2004
DOI: 10.1063/1.1828123
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities between rotating and stationary parallel disks with suction

Abstract: From visualizations, we study the patterns’ formation of the flow in a stationary cylinder driven by a rotating bottom disk when central suction is applied. That creates an annular axial jet at the cavity periphery which destabilizes and gives rise to instability patterns. We distinguish two types of instability patterns and study more particularly the one which takes place in the boundary layer of the cylindrical wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Moreover we showed that the mean radial and tangential velocity profiles exhibit inflection points, which is a characteristic of this type of instability. We have also shown that the SRJ2 spiral rolls are comparable to the structures denoted 2 by Rémy et al (2005), which are a crossflow instability attached to the axial jet: spirals with a small wavelength and a large wavenumber. The only discrepancy remains the inclination angle, which is much larger in our experiment, up to 72 • , which could be due to the radial gap.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Moreover we showed that the mean radial and tangential velocity profiles exhibit inflection points, which is a characteristic of this type of instability. We have also shown that the SRJ2 spiral rolls are comparable to the structures denoted 2 by Rémy et al (2005), which are a crossflow instability attached to the axial jet: spirals with a small wavelength and a large wavenumber. The only discrepancy remains the inclination angle, which is much larger in our experiment, up to 72 • , which could be due to the radial gap.…”
Section: Resultsmentioning
confidence: 56%
“…The flow is then mainly governed by the rotation. For high values of the axial velocity V z , the flow is governed by the throughflow and the SRJ2 patterns are comparable to the structures denoted 2 by Rémy (2004) and Rémy et al (2005). The main characteristics of structures 2 are a high wavenumber 40 6 k * 6 70 and a weak frequency N 6 3.5 Hz.…”
Section: Description Of the Srj2 Spiral Rollsmentioning
confidence: 58%
See 2 more Smart Citations
“…These subtle flow phenomena interact with the main flow and can threaten the efficiency and stable operation of centrifugal compressors (Qin, Sun, Wang, Ju, & Zhang, 2016). In earlier studies, the rotor and stationary components were simplified to a 'rotating stationary disk' problem to examine the flow structure in detail (Remy, Gauthier, & Buisine, 2005;Remy & Buisine, 2006;Jiao & Fu, 2016). However, in recent years, studies have focused on investigating the actual structure.…”
Section: Introductionmentioning
confidence: 99%